The psychology of relationship between squat's kinematics' variables, anthropometric measurements and jump serve kinematics' variables amongst volleyball players - Hammouri, W. A. L.; Ismail, W. T. B. (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The aim of the current study was to investigate the impact of the kinematic variables of squatting and anthropometric measurements on jump height, ball throwing angle and ball speed in jump serve amongst Jordanian volleyball players. The researcher used the descriptive method. Eight male volleyball players took part in this study. The researcher used an iPhone camera (30\sec) to record the players' performance. Marks were placed on the joints of the players in order to observe the kinematics of their jump serve. Kinovea © software was then used to analyze the jump serve and bodyweight squat. After data analysis (by means of multiple linear regression, one-way ANOVA, and standard deviation), it was concluded that body-mass, height, and BMI affect the jump height, and that squat depth does affect the throwing angle in the jump serve. It was also found that flexion time of the legs and arms do not affect ball speed during the serve. Therefore, it is recommended that volleyball training should focus more on strengthening the lower limbs.